2011
DOI: 10.1063/1.3549933
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of filtered Navier–Stokes equation for hybrid RANS/LES simulation

Abstract: Hybrid Reynolds-averaged Navier-Stokes/large eddy simulation ͑RANS/LES͒ is expected to accurately predict wall-bounded turbulent flows at high Reynolds numbers. It is known that extra terms due to the noncommutivity between the hybrid filter and the spatial derivative appear in the hybrid-filtered equations. In this paper the filtered Navier-Stokes equation is investigated using direct numerical simulation data of turbulent channel flow. In particular, the transport equations for the resolved and modeled energ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 34 publications
0
18
0
Order By: Relevance
“…Specifically, 105 uniform grid points on the domain [6π/2 − 0.059882471808, 6π/2] are mapped to the domain [0, 4π] through equation (12). The offset value is determined to ensure the points exactly span a 4π interval.…”
Section: Setupmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, 105 uniform grid points on the domain [6π/2 − 0.059882471808, 6π/2] are mapped to the domain [0, 4π] through equation (12). The offset value is determined to ensure the points exactly span a 4π interval.…”
Section: Setupmentioning
confidence: 99%
“…Nevertheless, correction of the commutation error is crucial for developing robust subgrid stress (SGS) models for practical LES applications. Furthermore, Hamba [12] showed that the impact of resolution inhomogeneity on hybrid RANS/LES applications can be significant because the resolution must change drastically when transitioning to/from LES and RANS regions. Modeling of commutation effects will, therefore, also be necessary for these more sophisticated turbulence modeling techniques, which inherit the deficiencies of the traditional SGS models they are based upon.…”
Section: Introductionmentioning
confidence: 99%
“…This filter passes frequencies up to 60Hz. Influence of higher harmonics on fi50 -angle (directly on sine and cosine of the angle) is avoided in this way which can be calculated next from so sine and cosine values prepared by using are tangent function [7]. where f 0 is mains frequency [8].…”
Section: Energy Hybrid Filter Of Inverter By-pass Switched Onmentioning
confidence: 99%
“…This turns SRS models grid dependent, precluding the evaluation of modeling and numerical errors separately, a requirement for reliable V&V exercises. Also, dynamic SRS formulations lead to commutation errors since the filtering operator of the model does not commute with spatial and temporal differentiation [50]. iv) Numerical setup -a precise validation exercise requires numerical simulations and reference experiments performed on the same flow conditions, i.e., domain, boundary conditions, material properties, and initial or inflow conditions.…”
Section: Introductionmentioning
confidence: 99%